Effects of prior compression on ductility and yielding behaviour in extruded magnesium alloy AZ31. (October 2014) - He, J. J.; Liu, T. M.; Chen, H. B.; Lu, L. W.; Pan, F. S.
<x content-type="archive" xml:space="preserve">Abstract</x> In the present paper, the effects of precompression along extrusion direction (ED) on subsequent compression perpendicular to ED were investigated in an extruded magnesium alloy AZ31. The results showed that the yield stress under compression perpendicular to ED increased if there was precompression along ED. The evolution of deformation mechanism was responsible for increase in yield stress because plastic deformation was dominated by both basal slip and {10–12} twinning under compression perpendicular to ED in samples without prestrain, but basal slip was difficult to be activated and {10–12} twinning dominated deformation in samples with precompression. However, because basal slip had no obvious contribution to plastic deformation, the ductility decreased if there was precompression along ED.